The 5 R’s: An Emerging Bold Standard for Conducting Relevant Research in a Changing World - Peek, C. J. (American Academy of Family Physicians, 2014)
Research often fails to find its way into practice or policy in a timely way, if at all. Given the current pressure and pace of health care change, many authors have recommended different approaches to make health care research more relevant and rapid. An emerging standard for research, the “5 R’s” is a synthesis of recommendations for care delivery research that (1) is relevant to stakeholders; (2) is rapid and recursive in application; (3) redefines rigor; (4) reports on resources required; and (5) is replicable. Relevance flows from substantive ongoing participation by stakeholders. Rapidity and recursiveness occur through accelerated design and peer reviews followed by short learning/implementation cycles through which questions and answers evolve over time. Rigor is the disciplined conduct of shared learning within the specific changing situations in diverse settings. Resource reporting includes costs of interventions. Replicability involves designing for the factors that may affect subsequent implementation of an intervention or program in different contexts. These R’s of the research process are mutually reinforcing and can be supported by training that fosters collaborative and reciprocal relationships among researchers, implementers, and other stakeholders. In sum, a standard is emerging for research that is both rigorous and relevant. Consistent and bold application will increase the value, timeliness, and applicability of the research enterprise.